Drugs as matrix to detect their own drug delivery system of PEG‐b‐PCL block copolymers in matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry. (2nd September 2013) - Knop, Katrin; Stumpf, Steffi; Schubert, Ulrich S.
Abstract : RATIONALE: The fate of drug delivery systems (DDSs) in vivo is a widely discussed question. Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) is an important tool to localize proteins and small compounds in many different tissues. This basic study was performed as an aid to obtain spatial information on DDSs in the future. METHODS: LDI and MALDI‐TOF MS was used to investigate five drug molecules, i.e. madurahydroxylactone (MHL), tetrakis(4‐hydroxyphenyl)porphyrin (THP), chartreusin (Chart), amphotericin B (AmB) and retinoic acid (RA). The drug molecules were analyzed in terms of their efficiency to act as matrix for different homopolymers and the block copolymer poly(ethylene glycol)‐ block ‐poly( ε ‐caprolactone) (PEG‐ b ‐PCL). The block copolymer was further utilized as a DDS to encapsulate the drug molecules previously investigated as matrices. The obtained DDSs were investigated by MALDI. RESULTS: The spectra obtained with the drugs Chart, MHL, THP and AmB did not reach the quality of the standard matrix RA. Nonetheless, they showed surprisingly good results as matrices for different homopolymers and the block copolymer. However, only the DDSs containing THP as the drug provided spectra where the drug and the block copolymer were detected. CONCLUSIONS: These results form the foundation for obtaining mass‐related information about the localization of DDSs and drugs in tissues. Copyright © 2013 John Wiley & Sons, Ltd.